Defect structure and percolation in the packing of bidispersed particles on a sphere - Mascioli, Andrew M. (Tufts Archival Research Center, 2017)
In this work, we study packings of bidispersed particles on spherical surfaces. The literature tells us that in the case of a uniform monodisperse packing, curvature necessitates a minimum number of defects to form. In the low bidispersity regime, the initial crystalline order is disrupted leading to an overall disordered packing. On the other hand in the high bidispersity regime, commensurate packing motifs such as the small particles fitting into the interstices of the large restore some order and promote a higher fill fraction compared to monodispersity. This variation in the packing fraction is explained by various geometric effects and a percolation transition of chains of non-hexatically coordinated particles that grow and eventually connect to disrupt the neighbor graph.